Disparities and change over time in distance women would need to travel to have an abortion in the USA: a spatial analysis - Jonathan M Bearak, Dr, PhD; Kristen Lagasse Burke, BA; Rachel K Jones, PhD (Elsevier, 2017)
Summary: Background: Abortion can help women to control their fertility and is an important component of health care for women. Although women in the USA who live further from an abortion clinic are less likely to obtain an abortion than women who live closer to an abortion clinic, no national study has examined inequality in access to abortion and whether inequality has increased as the number of abortion clinics has declined. Methods: For this analysis, we obtained data on abortion clinics for 2000, 2011, and 2014 from the Guttmacher Institute's Abortion Provider Census. Block groups and the percentage of women aged 15â44 years by census tract were obtained from the US Census Bureau. Distance to the nearest clinic was calculated for the population-weighted centroid of every block group. We calculated the median distance to an abortion clinic for women in each county and the median and 80th percentile distances for each state by weighting block groups by the number of women of reproductive age (15â44 years). Findings: In 2014, women in the USA would have had to travel a median distance of 10Â·79 miles (17Â·36 km) to reach the nearest abortion clinic, although 20% of women would have had to travel 42Â·54 miles (68Â·46 km) or more. We found substantially greater variation within than between states because, even in mostly rural states, women and clinics were concentrated in urban areas. We identified spatial disparities in abortion access, which were broadly unchanged, at least as far back as 2000. Interpretation: We showed substantial and persistent spatial disparities in access to abortion in the USA. These results contribute to an emerging literature documenting similar disparities in other high-income countries. Funding: An anonymous grant to the Guttmacher Institute.